In vitro evaluation of the marginal microleakage of amalgam restorations associated with dentin adhesive, glass ionomer cement and cavity varnish by means of different evaluation methods Avaliação in vitro da microinfiltração marginal em restaurações de amálgama associadas a adesivo dentinário, cimento de ionômero de vidro e verniz cavitário, utilizando diferentes métodos de avaliação - Adriano Tomio Hoshi; Salete Moura Bonifácio da Silva; Aymar Pavarini (University of São Paulo, 2005)
This in vitro study evaluated the marginal microleakage of amalgam restorations associated with the cavity varnish Copalite - Cooley & Cooley (GI-CP), dentin adhesive OptiBond Solo - Kerr (GII-OS) and the glass ionomer cement Vitremer - 3M (GIII-VT). Forty-five premolars were employed, which were submitted to independent class II preparations at the mesial and distal aspects comprising the marginal ridges and were restored with Dispersalloy - Dentsply. Afterwards, the teeth were thermocycled and stored in 0.5% basic fuchsine for 24 hours. The evaluations were conducted on a light microscope with 150x magnification and on the Sigma Scan software with employment of a single line and segmented lines. Data analysis allowed to establish that none of the materials was able to eliminate the marginal microleakage, having the GI - CP presented greater and statistically significant values in relation to the other groups in all evaluation methods (p<0.05). The lowest values were displayed by the GIII-VT, yet with no statistically significant difference when compared to GII-OS, except for the evaluation at the Sigma Scan in single line. The three evaluation methods showed a strong positive relationship to each other. Este trabalho avaliou, in vitro, a microinfiltração marginal de restaurações de amálgama associadas ao verniz cavitário Copalite - Cooley & Cooley (GI - CP), ao adesivo dentinário OptiBond Solo - Kerr (GII - OS) e ao CIV Vitremer - 3M (GIII - VT). Foram utilizados 45 pré-molares que receberam preparos cavitários independentes classe II nas faces mesial e distal, envolvendo as cristas marginais. Todas as cavidades foram restauradas com a liga Dispersalloy - Dentsply. Posteriormente, os dentes sofreram termociclagem e foram armazenados em solução de fucsina básica a 0,5% por 24 horas. As avaliações foram realizadas através de um microscópio óptico com aumento de 150 vezes e no software Sigma Scan, utilizando linha única e linhas segmentadas. A análise dos dados obtidos permitiu constatar que nenhum dos materiais foi capaz de eliminar a microinfiltração marginal, sendo que o GI - CP apresentou valores maiores e estatisticamente significantes (p<0,05) em relação aos demais grupos em todos os métodos de avaliação. Os menores valores foram obtidos pelo GIII - VT, porém sem diferença estatisticamente significante quando comparado ao GII - OS, exceto pela avaliação no Sigma Scan em linha única. Os três métodos de avaliação de medidas lineares empregados mostraram ter uma forte correlação positiva entre si.